Beta-thromboglobulin and platelet factor 4 levels in retinal vein occlusion. Issue 3 (March 1983) - Dodson, P M; Westwick, J; Marks, G; Kakkar, V V; Galton, D J
Abstract : Fifty-six patients with retinal vein occlusion–35 with central and 21 with branch vein occlusion–were investigated for comparison with an age and sex matched control group. Mean levels of beta-thromboglobulin and platelet factor 4 were significantly higher (p less than 0.001) in both the group with central and the group with branch retinal vein occlusion than in the control group. A significant increase of beta-thromboglobulin (p less than 0.001) was also found in the retinal vein occlusion group in those patients who were not hyperlipidaemic or diabetic (n = 39). Weak correlations were found between levels of lipoprotein cholesterol and plasma beta-thromboglobulin. Increased platelet aggregation may contribute to the aetiology of retinal vein occlusion.